Split Hand Syndrome in a Family with GARS -Associated Axonal Neuropathy - Kang, You-Ri; Kang, Kyung-Wook; Nam, Tai-Seung; Im, Jae-Hwan; Kim, Sang-Hoon; Lee, Seung-Jin (Journal of clinical neurology (Seoul, Korea), 2019)
KCI Citation Count: 2